The case of the love commandos [compact disc, unabridged] : from the files of Vish Puri, India's most private investigator - Hall, Tarquin (Hall, Tarquin. Vish Puri mystery., 2013)
When a young Indian couple--Ram and Deepa--fall in love, the young woman's parents are dead set against the union. She's from a high caste family. Her boyfriend is an Untouchable, a member of society traditionally doomed from birth to sweep the streets or worse. Deepa's father locks her up and promises to hunt down and kill the "loverboy dog." Fortunately, India's Love Commandos, a group of volunteers dedicated to assisting mixed caste couples, come to their rescue.